Securing a just and healthy future for all: Bringing a planetary health lens to the Earth System Governance research framework - Annabelle Workman; Giorgia Dalla Libera Marchiori; Godfred Boateng; Scott Carlin; Sharon Friel; Elise Moo; Rebecca Patrick; Alexandre San Martim Portes; Rosalind Warner; Kathryn Bowen (Earth System Governance)
Background: Governance efforts to address environmental degradation and consequent impacts on human health and wellbeing have had limited effectiveness to date. A unified planetary health approach that is holistic and integrates stewardship and alternative ways of knowing, being and doing may provide more successful governance pathways. Accordingly, we developed a research agenda intended to pursue transformational pathways that progress planetary health and embrace a modus operandi of stewardship across multiple governance levels. Methods: We used the 2018 Earth System Governance (ESG) research framework to guide a rapid review of the literature and establish a research agenda for planetary health within the context of earth system governance. We used a consensus process to support the identification and development of research questions. We developed a search strategy and used Scopus and PubMed to identify peer-reviewed literature published in English relating to planetary health and the four ESG contextual conditions: transformations, inequality, Anthropocene, and diversity. Results: 88 articles were included in the review. A majority were published between 2020 and 2023. Common topics included food systems and land use change, climate change, post-pandemic opportunities, as well as curriculum and research activities relating to planetary health. Systems and justice were key concepts. While interventions were commonly proposed in included articles, there was limited consideration of the role of governance. Conclusion: There remains scarce literature exploring fundamental questions on the relationship between planetary health and earth system governance. This presents an important opportunity to interrogate research questions pertaining to planetary health and earth system governance to support the urgent action. We propose initial questions that form the basis of a research agenda to extend our understanding of planetary health in the context of earth system governance.